High-performance electrochromic covalent hybrid frameworks membrane via a facile one-pot synthesis - Liu, Jian (2022)
Porous framework materials have sparked enormous interest in the electrochromic field as they possess intrinsic high porosity and large surface area that are beneficial for electron and ion transport. However, the fabrication of these porous framework materials often requires multiple processing steps or harsh reaction conditions, which significantly limit large-scale fabrication of such materials. In this work, we report a one-pot in situ polycondensation method to construct electrochromic covalent hybrid frameworks membrane via nucleophilic substitutions between hexachlorocyclotriphosphazene (HCCP) and triphenylamine (TPA) at ambient environment. With high transparency of polyphosphazene in a wide optical range, the constructed phosphazene-triphenylamine (PPTA) covalent hybrid frameworks membrane can be reversibly switched between light grey and dark blue, with a high transmittance change up to 79.8%@668 nm and fast switching time (< 4 s). Owing to the easy one-pot fabrication and good electrochromic properties, the PPTA covalent hybrid frameworks membrane has great potential in various fields such as displays and dynamic optical windows.